2021
DOI: 10.31584/jhsmr.2021816
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Postoperative Shivering at Post Anesthesia Care Unit in Normothermic Patients Underwent General Anesthesia

Abstract: Objective: The aim of study was to identify risk factors that can be modified to reduce incidence of postoperative shivering in normothermic patient who underwent general anesthesia.Material and Methods: A retrospective case control study was conducted between January 2017 and August 2018 by assessing the anesthetic records of normothermic patients at a post anesthesia care unit who underwent general anesthesia. A control group of 201 patients was randomly matched with 201 cases by age (±5 years) and site of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The study by Eberhart et al [7] confirmed the finding that longer duration of surgery as well as pyogenic substances released from injured tissue impaired the thermoregulatory system and induced shivering. Similarly, Laortip Rattanapittayaporn et al [29] , in their study identified higher BMI and shorter duration of surgery reduced risk of postoperative shivering. Irrigation fluid used during our study was at room temperature and thus its absorption causes perioperative hypothermia.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The study by Eberhart et al [7] confirmed the finding that longer duration of surgery as well as pyogenic substances released from injured tissue impaired the thermoregulatory system and induced shivering. Similarly, Laortip Rattanapittayaporn et al [29] , in their study identified higher BMI and shorter duration of surgery reduced risk of postoperative shivering. Irrigation fluid used during our study was at room temperature and thus its absorption causes perioperative hypothermia.…”
Section: Discussionmentioning
confidence: 76%
“…~ 87 ~ PCNL is a procedure where large quantity of irrigation fluid absorbed and thus again contribute to perioperative hypothermia and its complication. Prophylactic paracetamol infusion has been found to reduce the post-operative shivering [27][28][29] and nausea vomiting [19] . Here, we have also correlated incidence of post-operative shivering with patient's age, BMI, and amount of irrigation fluid.…”
Section: Discussionmentioning
confidence: 99%